Analysis of Power Dissipation and Breakdown Voltages of 200μm,3C-SiC Schottky Barrier Diodes - Singh, Manjeet (My University, 2012)
Silicon carbide is a wide band gap semiconductor material for high temperature, high power and high-frequency device applications. The fact that wide band gap semiconductors are capable of electronic functionality at much higher temperatures than silicon. Because of its wide band gap, the leakage current of SiC is many orders of magnitude lower than that of silicon. There are number of possible crystal structure. These are 2H, 3C, 4H and 6H; but the most important are 3C, 4H and 6H.These structures differ by band gap energy, carrier mobility and breakdown field. Silicon Carbide is the only chemical compound of carbon and silicon. It was originally produced by a high temperature electro-chemical reaction of sand and carbon. Schottky barrier diodes (SBDs) have many benefits compared to other rectifying devices, such as fast switching speeds and relatively easy fabrication. The present work aims at the design of high breakdown voltage and lower power dissipation 3C-SiC schottky barrier diode and study the effect of Power Dissipation, critical electric field ,breakdown voltage on Specific on Resistance for Uniformly doping profile and linearly graded profile. At the different value of current density Jon. After that the drift region depletion width is calculated at different doping levels. By using linearly graded profile, it is possible to design thinner devices with higher breakdown voltages and low Power dissipation.
Master of Technology (VLSI Design and CAD)
Keywords: 200μm,3C-SiC; Barrier Diodes; Breakdown Voltages